Local Color in the Novel Kidung di Tampun Juah by Liu Ban Fo: A Literary Anthropology Study - Maria Fransiska; Chairil Effendy; Sesilia Seli; Ahadi Sulissusiawan; Agus Wartiningsih (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study aims to describe the forms and meanings of local color in the novel Kidung di Tampun Juah by Liu Ban Fo through a literary anthropology approach. The method used is descriptive qualitative with an interpretative approach. Data were collected through documentation techniques, including close reading, note-taking, and coding. The data consist of textual excerpts containing elements of Dayak Iban Desa culture in West Kalimantan, with 17 excerpts selected purposively from a total of 35 initial data. Data analysis employed the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results show that local color in the novel is represented through seven cultural elements, namely the belief system, social system, knowledge system, language, arts, livelihood, and material culture. The novelty of this study lies in its analytical approach, which examines local color as an integrated and interconnected cultural system rather than as separate values. By applying Koentjaraningrat’s framework of seven cultural elements, this study provides a more comprehensive analysis in revealing the interrelationships among cultural elements within literary texts. In addition, this study introduces a relatively under-researched object, thereby contributing to the development of culture-based literary studies as well as the preservation of Dayak local culture through literature. Furthermore, the findings of this study can be utilized as teaching materials in literature learning to strengthen students’ understanding of local wisdom and Indonesia’s cultural diversity. The novel is also relevant for use in Grade 12 senior high school literature learning under the Merdeka Curriculum, particularly in Phase F learning outcomes related to the analysis of character, plot, and social context in prose works.